Is the ≥1 cm Width of the Resection Margin in Benign and Borderline Phyllodes Tumor Necessary to Reduce Recurrence? - Nattakarn Changchit; Natthawadee Laokulrath; Pradit Rushatamukayanunt; Pongthep Pisarnturakit (The Breast Journal)
Background. Phyllodes tumors (PTs) are fibroepithelial neoplasms of the breast, with current treatment guidelines recommending wide excision to achieve surgical margins of ≥1 cm to minimize the recurrence risk. However, diagnostic challenges with core biopsy specimens often result in suboptimal surgical margins. This study aims to elucidate the correlation between margin status and PT recurrence, thereby informing surgical decision-making and enhancing patient outcomes. Methods. This single-center, retrospective study reviewed records of Thai women diagnosed with PTs between 2011 and 2018, collecting data on demographics, clinical presentation, surgical approach, tumor grade, size, and margin status. The primary endpoint was recurrence. Results. Among 165 PT cases analyzed—49.1% borderline, 38.2% benign, and 12.7% malignant—the overall recurrence rate was 13.9% (n = 23) over a median follow-up of 4.5 years. No significant difference in recurrence rates was observed between patients with negative resection margins <1 cm (ranging from <1 mm to 9 mm) compared to those with ≥1 cm (10.2% vs. 7.1%, p=1.00). Notably, in negative resection margins <1 cm group, a margin <1 mm (close margin) was associated with a significantly higher recurrence rate compared to margins of 1–9 mm (17.0% vs. 4.9%, p=0.04). Borderline PTs followed the overall trend, while benign PTs showed increased recurrence with positive margins. Multivariate analysis indicated a significant association between margins <1 mm and recurrence (adjusted HR = 10.78 (95% CI 1.32–88.07), p=0.027), highlighting an increased recurrence risk with more extensive positive margins. Conclusion. Our findings suggest that a wide surgical margin of ≥1 centimeter may not be necessary to prevent recurrence in benign and borderline PTs. Notably, surgical margins narrower than 1 millimeter substantially elevate the recurrence likelihood in cases of borderline PTs. Furthermore, the presence of positive surgical margins correlates with an increased recurrence rate in benign PTs. These findings highlight the critical need for a strategic approach in determining surgical margins, tailored specifically to the type of PT, to enhance patient outcomes effectively.